Class inclusion concept development in children Effect of two curricular programs - Miao, Emily Shiao Chun Yui 1920- (1969)
This study investigates the development of the class inclusion concept in children on the basis of Inhelder's and Piaget's assumption of early growth of logic. The study focuses on the following: the development of classificatory logic among some Filipino Elementary school children as postulated by Piaget, and the possible effects of the two curricular programs on the attainment of the class inclusion concept.
Thesis (Ph.D.)--University of the Philippines, Diliman.
Keywords: Categorization (Psychology).; Cognition